Upaya Mengembangkan Perilaku Toleransi Pada Pendidikan Anak Usia Dini di TK Rausyan Kids - Syahputri, Nabila Dwi (EduInovasi: Journal of Basic Educational Studies, 2024)
Indonesia is a country that has diversity, with this diversity it has decorated the country of Indonesia from time to time. Early Childhood Children (AUD) also experience and face diversity, to the point that there are many polemics of prejudice including youth youngsters. A child's capital for interacting with other people is tolerance, which helps them appreciate diversity that is not their own. The point of this exploration is to foster better lenient conduct in youngsters at Rausyan Children Kindergarten. This research employs a descriptive qualitative approach. Meetings, documentation and perception are the data gathering procedures utilized in this review. The research results show that a tough personality can be formed through adaptation techniques in training, for example getting children used to interacting harmoniously, having a brotherly attitude, a caring attitude, a cooperative attitude, and setting a good example. The obstacles encountered in creating AUD tolerant behavior in Rausyan Kids Kindergarten are when dealing with children with special needs and problems between parents and educators.